Comparison of Local Recurrence Among Early Breast Cancer Patients Treated With Electron Intraoperative Radiotherapy vs Hypofractionated Photon Radiotherapy an Observational Study - Guenzi, Marina; Bonzano, Elisabetta; Corvò, Renzo; Merolla, Francesca; Pastorino, Alice; Cavagnetto, Francesca; Garelli, Stefania; Cutolo, Carlo Alberto; Friedman, Daniele; Belgioia, Liliana (Frontiers in Oncology, 2018)
PURPOSE: To evaluate local recurrence (LR) in women with early breast cancer (BC) who underwent intraoperative radiation therapy with electrons particles (IORT-E) or adjuvant hypofractionated external radiotherapy (HYPOFX). MATERIALS AND METHODS: We retrospectively analyzed 470 patients with early BC treated at our center from September 2009 to December 2012. 235 women were treated with breast-conserving surgery and immediate IORT-E (21 Gy/1 fraction) while 235 patients underwent wide excision followed by hypofractionated whole breast irradiation. Radiotherapy modality was chosen according an individualized decision based on tumour features, stage, technical feasibility, age, acceptance to be enrolled in the IORT-E group. RESULTS: After a median follow-up of 6 years, we observed 8 (3.4%) and 1 (0.42%) LR in the IORT-E and in the HYPOFX group (p=0.02), respectively. The two groups differed in the prevalence of clinical characteristics (p<0.05): age, tumor size, surgical margins, receptors, ki67 and histology. 4 and 1 women in the IORT-E and HYPOFX group died for breast cancer, respectively (p=0.167). OS and DFS hazard ratio [HR] were 2.14 (95% IC, 1.10 to 4.15) and 2.09 (95% IC, 1.17 to 3.73), respectively. CONCLUSIONS: Our comparison showed that IORT-E and HYPOFX are two effective radiotherapy modalities after conservative surgery in early BC. However, at 6 years a significant higher rate of LR occurred in patients submitted to IORT-E with respect to HYPOFX. This finding may be correlated to some subsets of patients who, depending on the biological characteristics of the BC, may be less suitable to IORT-E.